Acute Pharmacological Effects of 2C-B in Humans: An Observational Study - Papaseit, Esther; Farré, Magí; Pérez-Mañá, Clara; Torrens, Marta; Ventura, Mireia; Pujadas, Mitona; de la Torre, Rafael; González, Débora (Frontiers in Pharmacology, 2018)
2,5-dimethoxy-4-bromophenethylamine (2C-B) is a psychedelic phenylethylamine derivative, structurally similar to mescaline. It is a serotonin 5-hydroxytryptamine-2A (5-HT2A), 5-hydroxytryptamine-2B (5-HT2B) and 5-hydroxytryptamine-2C (5-HT2C) receptor partial agonist used recreationally as a new psychoactive substance (NPS). It has been reported that 2C-B induces mild psychedelic effects, although its acute pharmacological effects and pharmacokinetics have not yet been fully studied in humans. An observational study was conducted to assess the acute subjective and physiological effects, as well as pharmacokinetics of 2C-B. Sixteen healthy, experienced drug users self-administered an oral dose of 2C-B (10, 15, or 20 mg). Vital signs (blood pressure and heart rate) were measured at baseline 1, 2, 3, 4, and 6 hours (h). Each participant completed subjective effects using three rating scales: Visual Analogue Scales (VAS), the Addiction Research Centre Inventory (ARCI), and Evaluation of the Subjective Effects of Substances with Abuse Potential (VESSPA-SSE) at baseline, 2-3 h, and 6 h after self-administration (maximum effects along 6 h), and the Hallucinogenic Rating Scale (HRS) (maximum effects along 6 h). Oral fluid (saliva) was collected to assess 2C-B and cortisol concentrations during 24 h. Acute administration of 2C-B increased blood pressure and heart rate. Scores of scales related to euphoria increased (high, liking and stimulated), and changes in perceptions (distances, colors, shapes and lights) and different body feelings/surrounding were produced. Mild hallucinating effects were described in 5 subjects. Maximum concentrations of 2C-B and cortisol were reached at 1 h and 3 h after self-administration, respectively. Oral 2C-B at recreational doses induces a constellation of psychedelic/psychostimulant-like effects similar to those associated with serotonin-acting drugs.